Digital Currency under the Perspective of Islamic Law - Achmad Fageh (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
Fatwa Number: 28/DSn-MUI/III/2002 regulates the sale and purchase of money in the fatwa which reads: Currency buying and selling transactions are basically allowed, provided that: Not for chancy (speculation), just in case (savings), the transaction needs if the currency transactions are of the same type, they must be of the same value and cash. If different types, it must be based on the exchange rate at the time of transaction and cash delivery. The concept of digital currency for buying and selling transactions has met the requirements and pillars. However, in the mechanism, there is an element of ambiguity. Its nature and form is unknown (jahalah), which is contained in the software. The use of digital money is also seen as having many disadvantages. The reason is that when the price goes up, this digital money will be sold, and even the price can go up to zero. Here there is a dark side that is to draw fate and make a profit. So to avoid harm, this digital money is not recommended to be used.